SEX HORMONES CHANGES ASSOCIATED WITH MENSTRUAL CYCLE IN HIV INFECTED FEMALES AT NAUTH, NNEWI, SOUTHEAST NIGERIA - Ukibe, Nkiruka .R.; Emelumadu, Obiagel .F.; Ukibe, Solomon .N.; Onyenekwe, Charles.C.; Ahaneku, Joseph .E.; Aboh, Nancy .A.; Nnadozie, Okwudili J (European Scientific Journal, ESJ, 2015)
Background: The association of Human Immune deficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) and sex hormone changes may grossly affect the reproductive health in affected women. This was a prospective study done at Nnamdi Azikiwe University Teaching Hospital Nnewi, Anambra State, Nigeria to evaluate the sex hormone changes in HIV infected women of reproductive age group during menstrual cycle. Materials and methods: A total of 90 women (60 HIV positive, 30 Control) were studied. After detailed medical examination, a well-structured questionnaire was self-administered. Blood samples were collected under sterile conditions during the follicular and luteal phases of menstrual cycle after due informed consent had been sought and obtained. The samples were analyzed for sex hormones (Progesterone, estradiol and testosterone) using Enzyme Linked Immunosorbent Assay (ELISA) method. Results: The result showed that the sex hormones (Progesterone, estradiol and testosterone) were significantly lower at both phases of the menstrual cycle in HIV infected women when compared to the Control (P<0.05). Conclusion: The study revealed some degree of hypogonadism in HIV infected women which may have some implication in their reproductive life.